2013
DOI: 10.5402/2013/137045
|View full text |Cite
|
Sign up to set email alerts
|

Visiting Policies in the Adult Intensive Care Units in the Netherlands: Survey among ICU Directors

Abstract: Introduction. Admission to the ICU is a significant event for patients and their families and is often accompanied by stress, anxiety and depression. Literature shows that implementation of “unrestricted visiting policy” (UP) can potentially alleviate psychologically distressing elements of ICU admission.Methods. A web-based questionnaire was sent to all ICU’s concerning three main topics: general ICU information, detailed visiting policy information, and rationale for the chosen policy.Results. 87.1% of ICU’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
5
0
3
Order By: Relevance
“…However, liberal visitation policy reduces stress in patients and families and leads to significant improvement in patients. 15…”
Section: Discussionmentioning
confidence: 99%
“…However, liberal visitation policy reduces stress in patients and families and leads to significant improvement in patients. 15…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that patients prefer flexible visiting strategies. Open visiting hours realize the families’ needs and have a positive impact on the patients, improve patient satisfaction and may even reduce the stay in hospital ( Davidson et al, 2007 ; Noordermeer, Rijpstra, Newhall, Pelle, & van der Meer, 2013 ; Soumagne et al, 2011 ; Whitton & Pittiglio, 2011 ). Gonzalez et al (2004) have shown that visiting is a non-stressful experience for visitors.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the family also provide more effective feedback to patients than nurses and doctors, which lead to better working conditions. Family members can be politely asked to temporarily leave the room in urgent cases or for specific procedures ( Garrouste-Orgeas et al, 2008 ; Noordermeer et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ten years later, open visitation in US hospitals recognised for nursing excellence was only 18.6% ( Milner et al, 2020 ). Outside the US a similar pattern of restrictive visitation has been observed ( Garrouste-Orgeas et al, 2016 , Giannini et al, 2008 , Haghbin et al, 2011 , Noordermeer et al, 2013 ) despite being recommended by World Federation of Critical Care Nurses ( WFCCN Review Group, 2019 ).…”
Section: Introductionmentioning
confidence: 69%